Expanding the phenotypic spectrum of FINCA (fibrosis, neurodegeneration, and cerebral angiomatosis) syndrome beyond infancy. Issue 4 (14th July 2021) - Rapp, Christina K.; Van Dijck, Ine; Laugwitz, Lucia; Boon, Mieke; Briassoulis, George; Ilia, Stavroula; Kammer, Birgit; Reu, Simone; Hornung, Stefanie; Buchert, Rebecca; Sofan, Linda; Froukh, Tawfiq; et al.
Abstract: Fibrosis, neurodegeneration, and cerebral angiomatosis (FINCA, MIM#618278) is a rare clinical condition caused by bi‐allelic variants in NHL repeat containing protein 2 ( NHLRC2, MIM*618277). Pulmonary disease may be the presenting sign and the few patients reported so far, all deceased in early infancy. Exome sequencing was performed on patients with childhood interstitial lung disease (chILD) and additional neurological features. The chILD‐EU register database and an in‐house database were searched for patients with NHLRC2 variants and clinical features overlapping FINCA syndrome. Six patients from three families were identified with bi‐allelic variants in NHLRC2 . Two of these children died before the age of two while four others survived until childhood. Interstitial lung disease was pronounced in almost all patients during infancy and stabilized over the course of the disease with neurodevelopmental delay (NDD) evolving as the key clinical finding. We expand the phenotype of FINCA syndrome to a multisystem disorder with variable severity. FINCA syndrome should also be considered in patients beyond infancy with NDD and a history of distinct interstitial lung disease. Managing patients in registers for rare diseases helps identifying new diagnostic entities and advancing care for these patients. Abstract : Newly identified bi‐allelic in NHLRC2 expand the phenotypic spectrum of FINCA (F ibrosis, N eurodegeneration, C erebral A ngiomatosis) syndrome beyond infancy.